Computationally efficient solution for multilayer microwave circuits - Balik, Hasan H. (My University, 2003)
The Spectral Domain Method (SDM) is widely applied to analyse two layer planar microwave circuits. Adaptation of this technique to multilayer structures requires an efficient derivation of the Green's function. This paper provides an iterative derivation for computer design tool programmers.
Keywords: Iterative solution; Multilayer; Spectral Domain Method (SDM)